PD-L1 Testing, Treatment Patterns, and Clinical Outcomes Among Patients with Metastatic NSCLC at an Academic Medical Center, 2017–2021 - Mehmet Altan; Dawen Sui; Cai Xu; George R. Simon; Saliha T. Sulihem; Donna Malveaux; Darcy Ponce; Waree Rinsurongkawong; Vadeerat Rinsurongkawong; J. Jack Lee; Jianjun Zhang; Don L. Gibbons; et al. (Journal of Immunotherapy and Precision Oncology)
Introduction Targeted therapies and immune checkpoint inhibitors (ICIs) have revolutionized the management of metastatic non–small cell lung cancer (NSCLC) over the past decade. Methods This single-center observational study was conducted to describe programmed death-ligand 1 (PD-L1) testing, choice of therapy, and outcomes for adult patients with stage IV NSCLC initiating first-line therapy from 2017 through 2020, with follow-up through June 2021. Patient characteristics and study assessments were described according to four histomolecular subtypes, defined by histologic characteristics and availability of standard-of-care therapies for molecular subgroups at the time of study conduct. Results Of 507 eligible patients with metastatic NSCLC, 85 (17%) had squamous NSCLC; 288 (57%) had nonsquamous NSCLC with no actionable genomic alteration; 44 (9%) had nonsquamous NSCLC with KRAS G12C mutation; and 90 (18%) had nonsquamous NSCLC with ROS1, BRAF V600E, EGFR exon 20 insertion, or RET or NTRK genomic alteration. Most tumors were PD-L1 tested. After excluding 40 patients whose PD-L1 testing status was unknown, all but 55 tumors (12%) were tested for PD-L1 expression, and the percentages tested rose from 86% in 2017 to 100% in 2020. From 27% of nonsquamous NSCLC with no actionable genomic alteration to 46% of KRAS G12C-mutated NSCLC had PD-L1 expression ≥ 50%. Use of chemotherapy decreased and use of ICI-chemotherapy combinations increased from 2017 to 2020. In the squamous NSCLC group, single or combination chemotherapy was administered most commonly (42%), whereas ICI-chemotherapy combinations were the most common first-line regimens in the three nonsquamous NSCLC histomolecular groups. For patients with NSCLC and no actionable genomic alterations, ICI-chemotherapy combinations were the most common regimens in 2018–2020 in all but the PD-L1 ≥ 50% category, for whom ICI monotherapy was most common every year except 2020. Median overall survival was 25.0 months (95% CI, 19.1–28.3) for all patients, and, by histomolecular cohort, 14.3 months for squamous NSCLC, 25.3 months for nonsquamous NSCLC with no actionable genomic alteration, not reached for KRAS G12C-mutated NSCLC, and 27.7 months for nonsquamous NSCLC with other genomic alterations. Conclusion Study findings highlight the increased use of PD-L1 testing over the years from 2017 to 2020 and recent changes in therapy, with decreased use of chemotherapy and increased use of ICI-chemotherapy combinations during the study in each histomolecular group. Moreover, we observed improvements in survival for patients with metastatic NSCLC relative to historical real-world data.